Crystal structure of monoclinic calcium pyrophosphate dihydrate (m‐CPPD) involved in inflammatory reactions and osteoarthritis. Issue 1 (1st February 2016) - Gras, Pierre; Rey, Christian; André, Gilles; Charvillat, Cédric; Sarda, Stéphanie; Combes, Christèle
Abstract : Rietveld refinement of complementary synchrotron powder X‐ray diffraction and neutron diffraction data leads to the resolution of the structure of the monoclinic phase of calcium pyrophosphate dihydrate (m‐CPPD) including the determination of the precise position of the hydrogen atoms. These new structural data are of particular importance to further understand in vivo phenomena related to osteoarthritis: m‐CPPD phase formation and evolution, and structure–inflammatory response relationships. Abstract : Pure monoclinic calcium pyrophosphate dihydrate (m‐CPPD) has been synthesized and characterized by synchrotron powder X‐ray diffraction and neutron diffraction. Rietveld refinement of complementary diffraction data has, for the first time, allowed the crystal structure of m‐CPPD to be solved. The monoclinic system P 21 / n was confirmed and unit‐cell parameters determined: a = 12.60842 (4), b = 9.24278 (4), c = 6.74885 (2) Å and β = 104.9916 (3)°. Neutron diffraction data especially have allowed the precise determination of the position of H atoms in the structure. The relationship between the m‐CPPD crystal structure and that of the triclinic calcium pyrophosphate dihydrate (t‐CPPD) phase as well as other pyrophosphate phases involving other divalent cations are discussed by considering the inflammatory potential of these phases and/or their involvement in different diseases. These original structural data represent a key step in the understanding of the mechanisms of crystal formation involved in different types of arthritis and to improve early detection of calcium pyrophosphate (CPP) phases in vivo .